2012
DOI: 10.1016/j.pt.2012.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Do malaria parasites manipulate mosquitoes?

Abstract: Malaria parasites have been suggested to alter the behavior of mosquito vectors to increase the likelihood of transmission. Some empirical evidence supports this hypothesis, yet the role of manipulation is ignored in most epidemiological models, and behavioral differences between infected and uninfected females are not considered in the development or implementation of control measures. We suggest that this disconnect exists because the link between behavioral alteration and actual transmission in the field ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(95 citation statements)
references
References 50 publications
(56 reference statements)
4
91
0
Order By: Relevance
“…It is likely that the existing literature contains both false negative and false positive reports, and unbiased screenings of a broad number of parasite species are very difficult, due to the broad diversity of possible manipulation effects that would have to be considered. Negative reports are rare (but see, for example; Cator et al, 2012Cator et al, , 2013Cator et al, , 2015Soh et al, 2013;Berret and Voordouw, 2015;Vantaux et al, 2015) and many cases of manipulating parasites might as yet remain undiscovered, either because they lead to inconspicuous or no alterations in the phenotype of the host, or because certain classes of parasites are seldom studied for host manipulation. By contrast, false positive reports can arise because alternative explanations for the observed phenotypic alterations are usually not excluded.…”
Section: Searching For General Patterns In Reports On Host Manipulationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely that the existing literature contains both false negative and false positive reports, and unbiased screenings of a broad number of parasite species are very difficult, due to the broad diversity of possible manipulation effects that would have to be considered. Negative reports are rare (but see, for example; Cator et al, 2012Cator et al, , 2013Cator et al, , 2015Soh et al, 2013;Berret and Voordouw, 2015;Vantaux et al, 2015) and many cases of manipulating parasites might as yet remain undiscovered, either because they lead to inconspicuous or no alterations in the phenotype of the host, or because certain classes of parasites are seldom studied for host manipulation. By contrast, false positive reports can arise because alternative explanations for the observed phenotypic alterations are usually not excluded.…”
Section: Searching For General Patterns In Reports On Host Manipulationmentioning
confidence: 99%
“…As a possible explanation, he suggested publication bias, that is, an initial euphoria concerning the intensity of manipulation effects became replaced by more realistic estimates over time (Poulin, 2000). More recently, other authors have stressed that alternative explanations need to be considered-and excluded-to provide conclusive empirical support for an assumed case of manipulation (Klein, 2005;Thomas et al, 2005;James, 2010;Cator et al, 2012Cator et al, , 2015Lafferty and Kuris, 2012;Worth et al, 2013). Alternatively, such alterations can: (1) represent mere side-effects of the pathology that is associated with infection; (2) form part of the successful immune response of the host to parasitization; or (3) represent traits that were inherited from ancestors but represent maladaptations in the present host-parasite combination (Klein, 2005;Thomas et al, 2005).…”
Section: Searching For General Patterns In Reports On Host Manipulationmentioning
confidence: 99%
“…Combining data for these two species to estimate vital rates would not necessarily generate realistic inference. Furthermore, data and research are particularly needed to better understand the influence of environmental factors on key parameters such as the EIP [89], vector competence [94,113], biting behaviour and interactions with infection [118,119], because these have been very under-researched to date.…”
Section: (B) Challenges In Understanding Climate Change Effects On Vementioning
confidence: 99%
“…To optimize Plasmodium transmission, malaria-infected mosquito vectors carrying transmissible stages (sporozoites) should preferentially bite non-infected hosts, while infected hosts carrying transmissible stages (gametocytes) should be more attractive to healthy vectors than hosts without transmissible stages. Various studies in non-human systems indeed demonstrated altered mosquito feeding behaviour such as probing, persistence and engorgement rate upon Plasmodium infection (Hurd, 2003), suggesting manipulation of mosquito vectors by Plasmodium (Cator et al, 2012). Anopheles gambiae mosquitoes infected with sporozoites also showed increased attraction to the odour of healthy humans compared to non-infected mosquitoes .…”
Section: Manipulation Of Vertebrate Hosts By Plasmodium Parasitesmentioning
confidence: 99%
“…Other examples of manipulation are seen in Trypanosome-infected tsetse flies, which probe more frequently on vertebrate hosts than their non-infected counterparts (Roberts, 1981), thus increasing parasite transmission. Manipulation of mosquitoes by Plasmodium parasites, through direct effects in the mosquito, has been reviewed in detail (Koella et al, 1998;Lefèvre & Thomas, 2008;Cator et al, 2012) and will be briefly introduced below.…”
Section: Introductionmentioning
confidence: 99%